1974
DOI: 10.1111/j.1365-2621.1974.tb02906.x
|View full text |Cite
|
Sign up to set email alerts
|

The Aroma of Canned Beef: Processing and Formulation Aspects

Abstract: The influence of processing techniques and formulations on chemical and sensory aroma properties has been studied with the purpose of finding ways to improve the flavor of canned meat. HTST‐sterilization, “aseptic” canning and sterilization in various packaging materials including flexible pouches have been investigated. It was found that “aseptic” canning and, especially, HTST‐sterilization had a pronounced positive effect on aroma, in the latter case for samples packed in thin layers (flexible pouches). It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Literature data for odor thresholds are included in Table . The selection of compounds for Table III has been made from the odor point of view. Thus, the odor threshold data and the results from the investigation on canned beef (Persson and von Sydow, 1973von Sydow, , 1974aPers-son et al, 1973a,b) were used when selecting the compounds. This does not mean that all compounds are of importance for the odor, only that they are of a potential interest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature data for odor thresholds are included in Table . The selection of compounds for Table III has been made from the odor point of view. Thus, the odor threshold data and the results from the investigation on canned beef (Persson and von Sydow, 1973von Sydow, , 1974aPers-son et al, 1973a,b) were used when selecting the compounds. This does not mean that all compounds are of importance for the odor, only that they are of a potential interest.…”
Section: Resultsmentioning
confidence: 99%
“…This investigation deals with the aroma properties of heat treated protein food models containing different amounts of unconventional proteins and it is directly linked to another investigation on canned beef (Persson and von Sydow, 1973von Sydow, , 1974aPersson et al, 1973a,b).…”
mentioning
confidence: 99%
“…Sensory scores for appearance of the product had declined slowly from 7.6 to 6.2 based on 8 point hedonic scale in 90 days of storage. Similarly Persson and Sydow (1974) reported that the appearance of canned beef became lighter in color and more reddish during storage. Significant and gradual decline of flavor scores from 7.3 to 6.1 during storage was observed.…”
Section: Quality Changes During Storagementioning
confidence: 95%
“…The amount of volatile compounds giving aroma increases as heating temperature rises (Beltz et al 2004). Persson and Sydow (1974) reported that the meaty aroma was stronger in 121°C-heated beef than 115°C-heated beef. The results in this study indicate that generation of retort beef aroma is influenced by heating temperature and is enhanced at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%